ARHI as a key regulator of EMT and metastasis in pancreatic cancer via the Notch-1 pathway - Jingjing Liu; Yiqun Zhao; Ying Wang; Ying Shi; Qiang Zhi; Linlin Chen; Yuhao Ke; Jianlin Ren (Human Genetics, 2026)

Numerical simulation of regenerative accumulator for CO2 heat pump system in electric vehicles - Linlin Wang; Jiabao Ren; Rujie Yu; Baomin Dai; Tonghua Zou (International Journal of Refrigeration, 2026)

Building damage-matched ground motion generation method using physics-guided generative adversarial networks - Qingle Cheng; Haotian Ren; Hongyu Zhao; Aiqun Li; Linlin Xie (Engineering Structures, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

Dose- and time-dependent cardioprotection of liproxstatin-1 via sequential modulation of ferroptosis pathways after myocardial ischemia-reperfusion - Ziwei Huang; Xixi Chen; Junyi Ren; Linlin Wan; Miao Li; Xiaowu Ma; Jing Dong; Hong Ran (Molecular and Cellular Biochemistry, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Association of prenatal exposure to polychlorinated biphenyls with cleft lip and/or palate risk in offspring: A case-control study - Sainan Li; Shujian Lin; Yongyan Chen; Yiqi Ding; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Environmental Sciences, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Non-isothermal kinetic study on the roasting system of waste LiNixCoyMn1-x-yO2 battery powder-sulfamic acid - Zhenning Liu; Zhenan Jin; Linlin Tong; Xiaohang Ren; Guorui Hou (Process Safety and Environmental Protection, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

The Key Role of Somatostatin Neurons in the Suprachiasmatic Nucleus in Anxiety-Depression Comorbidity Following Sleep Deprivation - Yifei Zhang; Yuxin Wang; Xinyue Liu; Chunlin Ren; Ming Chen; Linlin Bi (Molecular Neurobiology, 2026)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Improving forest gross primary productivity estimation through climate and trait integration - Hongge Ren; Li Zhang; Min Yan; Bo Zhang; Linlin Ruan (Ecological Modelling, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

Organotin exposure and DNA methylation in non-syndromic cleft lip and palate: Integrating findings from case-control studies and animal experiments - Yongyan Chen; Qianhui Cheng; Sainan Li; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2024)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

Simulation of diffusion of combustible refrigerants R1234yf and R290 leakage in automotive air conditioning - Linlin Wang; Yu He; Jiabao Ren; Dan Wang; Baomin Dai; Zhe Zhang (International Journal of Refrigeration, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Prenatal co-exposure to phthalate metabolites and bisphenols among non-syndromic cleft lip and/or palate in offspring - Sainan Li; Haiyan Zhu; Chen Yang; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Exploring the paradox of densification and greening in China’ s old cities - Wenqi Chen; Yuxuan Qiu; Linlin Ruan; Chun Ren; Chunfeng Zhou; Sucheng Xu; Kechao Wang; Tingting He; Wu Xiao (Urban Forestry & Urban Greening, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

Recent Holocene activity and regional tectonic significance of the northern segment of the red river fault zone - Long Guo; Zhongtai He; Zhikun Ren; Linlin Li; Xingao Li; Haomin Ji; Kuan Liang; Xin Tan (Journal of Structural Geology, 2024)

Spatial distribution and regional tectonic significance of the newly discovered Kalawenguquan fault in the interior of the Tian Shan Mountain Range, Western China - Xingao Li; Zhongtai He; Zhikun Ren; Linlin Li; Lei Wang; Haomin Ji; Xiaoxiao Zhu; Long Guo; Liangliang Wu (Journal of Asian Earth Sciences, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

In Utero Exposure to Lead is Associated with Neural Tube Defects via Disturbing the Expression of Endocannabinoid Retrograde Signaling-Related Genes - Tian Tian; Huijun Dong; Shengju Yin; Mengyuan Liu; Yongyan Chen; Kuanhui Xiang; Linlin Wang; Jie Qiao; Aiguo Ren (Exposure and Health, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Rapid seismic-damage assessment method for buildings on a regional scale based on spectrum-compatible data augmentation and deep learning - Qingle Cheng; Aiqun Li; Haotian Ren; Cheav Por Chea; Wenjie Liao; Linlin Xie (Soil Dynamics and Earthquake Engineering, 2024)

A comprehensive study on the co-removal of Cr (VI) and ciprofloxacin via microbial-photocatalytic coupling: Mechanistic insights and performance evaluation - Yilin Dong; Qiuwen Wang; Jinyu Zhu; Linlin Liang; Dongyu Xu; Xueyue Mi; Zhijun Ren; Pengfei Wang (Journal of Environmental Management, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

A novel lateral epitaxial Bi2O3@BiOCl heterostructure for photocatalytic antibiotic degradation in an internal circulation fluidized bed reactor - Yilin Dong; Shaoxuan Pang; Fuqiang Zhang; Dongyu Xu; Qiuwen Wang; Kang Wang; Lijun Zhang; Linlin Liang; Zhijun Ren; Pengfei Wang (Chemical Engineering Journal, 2023)

Associations among bisphenol A, its analogs, and chlorinated derivatives in placenta and risk for neural tube defects: A case-control study - Haiyan Zhu; Qianhui Cheng; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2023)

Damping, soft, and thermally conductive composite elastomer via introducing bottlebrush chains - Shipeng Rao; Xiangliang Zeng; Xiaxia Cheng; Jianfeng Fan; Dongyi He; Linlin Ren; Guoping Du; Xiaoliang Zeng (Chemical Engineering Journal, 2023)

On the effects of rheological behavior on landslide motion and tsunami hazard for the Baiyun Slide in the South China Sea - Zhiyuan Ren; Hua Liu; Linlin Li; Yuchen Wang; Qiliang Sun (Landslides, 2023)

Prognostic value of the WT-1 gene combined with recurrent cytogenetic genes in acute myeloid leukemia - Qing Zhang; Linlin Liu; Haotian Yan; Xiyang Ren; Mei Zhou; Shudao Xiong; Huiping Wang; Qianshan Tao; Zhimin Zhai (Immunogenetics, 2023)

A preliminary study to explain how Streptomyces pactum (Act12) works on phytoextraction: soil heavy metal extraction, seed germination, and plant growth - Nina Wang; Jie Ren; Linlin Wang; Yuheng Wang; Ze Wang; Di Guo (Environmental Monitoring and Assessment, 2023)

Exploring the seasonality of surface urban heat islands using enhanced land surface temperature in a semi-arid city - Liying Han; Linlin Lu; Peng Fu; Chao Ren; Meng Cai; Qingting Li (Urban Climate, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Prenatal exposure to silver is associated with an elevated risk for neural tube defects: a case–control study - Xin Pi; Chengrong Wang; Di Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Wentao Yue; Chenghong Yin; Aiguo Ren (Environmental Science and Pollution Research, 2022)

Extensive Interspecific Gene Flow Shaped Complex Evolutionary History and Underestimated Species Diversity in Rapidly Radiated Dolphins - Weijian Guo; Di Sun; Yang Cao; Linlin Xiao; Xin Huang; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Mammalian Evolution, 2022)
Recently diverged taxa are often characterized by high rates of hybridization, which can complicate phylogenetic reconstruction. For this reason, the phylogenetic relationships and evolutionary history of dolphins are still not very well resolved; the question of whether the genera Tursiops and Stenella are monophyletic is especially controversial. Here, we performed re-sequencing of six dolphin genomes and combined them with eight previously published dolphin SRA datasets and six whole-genome datasets to investigate the phylogenetic relationships of dolphins and test the monophyly hypothesis of Tursiops and Stenella . Phylogenetic reconstruction with the maximum likelihood and Bayesian methods of concatenated loci, as well as with coalescence analyses of sliding window trees, produced a concordant and well-supported tree. Our studies support the non-monophyletic status of Tursiops and Stenella because the species referred these genera do not form exclusive monophyletic clades. This suggests that the current taxonomy of both genera might not reflect their evolutionary history and may underestimate their diversity. A four-taxon D -statistic (ABBA-BABA) test, five-taxon D FOIL test, and tree-based PhyloNet analyses all showed extensive gene flow across dolphin species, which could explain the instability in resolving phylogenetic relationship of oceanic dolphins with different and limited markers . This study could be a good case to demonstrate how genomic data can reveal complex speciation and phylogeny in rapidly radiating animal groups.

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Enhanced mass transfer and service time of mesh Ti/Sb-SnO2 electrode for electro-catalytic oxidation of phenol - Linlin Huang; Da Li; Junfeng Liu; Lisha Yang; Changchao Dai; Nanqi Ren; Yujie Feng (Environmental Science and Pollution Research, 2020)

Somatic mutations in planar cell polarity genes in neural tissue from human fetuses with neural tube defects - Tian Tian; Yunping Lei; Yongyan Chen; Menuka Karki; Lei Jin; Richard H. Finnell; Linlin Wang; Aiguo Ren (Human Genetics, 2020)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Modified Nonparametric Weighted Feature Extraction Algorithm - Linlin Cui; Guosheng Li; Huiru Ren; Lei He; Huajun Liao (Journal of the Indian Society of Remote Sensing, 2015)

Multi-scale variability of water discharge and sediment load into the Bohai Sea from 1950 to 2011 - Huiru Ren; Guosheng Li; Linlin Cui; Lei He (Journal of Geographical Sciences, 2015)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Effect of mechanical stretch on the expressions of elastin, LOX and Fibulin-5 in rat BMSCs with ligament fibroblasts co-culture - Zhao Bing; Liang Linlin; Yan Jianguo; Ren Shenshen; Ren Ruifang; Zhang Xi (Molecular Biology Reports, 2012)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)